Colación de las Metamorfosis de Ovidio en el ms. Turonensis 879 - Martel Bravo, Gabriel (Exemplaria Classica, 2010)
A reading of the extensive corpus of mss. containing the Metamorphoses of Ovid is an essential task for a better understanding of the manuscript tradition and the fixing of the text of this work. The present article offers a complete collation of the text of the Metamorphoses in ms. Turonensis 879 (s. XII-XIII). The collation is preceded by an introduction analysing the use of this codex in the different editions of Met. and highlighting some of its main characteristics and potential contributions, as well as pointing to possible relationships with other mss. and with the texts and commentaries of the edd. vett.